Signifikansi memahami Logika Dasar - M. idrus H. Ahmad (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
asically human being poses intelligence as a device to think in order to  achieve their purposes in life whether personal, group, or communal purposes. To  think without a depth and serious process is known as “ logical naturalist”. It  means that one thinks in a very simple and natural ways. When intelligence  contemplates a complex problem, it is called “logical artificial” that uses tight  logical procedure and logical science or is known in Islam as “Mantiq”. One of  fundamental differentiation between human being from animal is that the ratio  potential (natiq). The ratio activities on the subject, understanding written or  spoken word (lafaz), defining, proposing, opposing, sampling or analogy, forming  and syllogism result to a true and precise conclusion.